Effects of He irradiation on the microstructure and thermal conductivity of SiC - Wantong Sun; Shouxi Gu; Baolong Ji; Qiang Qi; Hai-Shan Zhou; Guang-Nan Luo (Nuclear Fusion)
SiC is considered as a structural and functional material in fusion reactors due to its exceptional radiation resistance, chemical inertness, and low neutron absorption cross-section. When exposed to high-energy neutrons, energetic helium ions are produced in SiC through transmutation reactions, which can significantly influence its microstructure and thermal conductivity. This study investigates the microstructure and thermal conductivity of SiC irradiated with helium ions. Grazing incidence x-ray diffraction (XRD) patterns reveal lattice spacing expansion and tensile strain induced by irradiation. Raman spectra indicate that irradiation severely breaks the SiC _4 tetrahedral units. Transmission electron microscopy imaging and selected area electron diffraction confirm that irradiation induces structural damage, helium bubble formation, and amorphization, consistent with the findings of XRD and Raman spectroscopy. The time-domain thermoreflectance method was employed to characterize the thermal conductivity of the irradiated layer. The results demonstrate a fluence-dependent degradation of thermal conductivity with increasing fluences. Specifically, the thermal conductivity decreased from approximately 190 W (m·K) ^−1 for unirradiated SiC to around 4.65 W (m·K) ^−1 at a fluence of 2 × 10 ^17 ions cm ^−2 (5.46 dpa). This trend clearly links the accumulation of defects and the degree of amorphization to increased phonon scattering, which is responsible for the reduction in thermal conductivity.